Water sorption and solubility of two acrylic resin denture base materials polymerized by Infrared radiation - Aliaa W Alomari; Nagham H Kassab; Nada Z Mohammed (University of Mosul, College of Dentistry, 2019)
Aims: To determine the effect of different curing times of a new method of polymerization by infrared radiation on the absorption and solubility in water of acrylic resin materials for denture base. Materials and Methods: In this study two types of denture base materials cured by heat were used (Traditional or Conventional and High Impact), the entire number of prepared specimens were (80) which grouped into: A- Control group: Consisted of two types of acrylic resin specimens polymerized by conventional water bath .B- Experimental group: Consisted of two types acrylic resin specimens polymerized by infrared radiation (IR) at different times of curing cycles. In each group; specimens were divided equally, some related to water sorption test others for solubility test. The mean of mass change of the material after they saturated with water and dried out of it was used, then analysis of data was done using one-way analysis of variance and Duncan test. Results: Statistically, no significant differences existed between Traditional and High Impact acrylic resin cured by water bath in water sorption and solubility tests. The means values for previously mentioned tests in two types of acrylic resin had been decreased significantly by changing type of curing from conventional water bath to (IR) method. Conclusions: The selection of appropriate time and type of curing method may optimize the level of absorption and solubility in water for previously mentioned materials.